Autopsy Procedure in Investigation of Deaths Related to Anesthesia Malpractice Allegations - Ertan, Ayşegül; Pakiş, Işıl (The Bulletin of Legal Medicine, 2006)
Retrospective studies about perioperative deaths show that most of deaths are due to the patients’ underlying disease and surgical intervention. Death cases solely due to perioperative anesthesia are observed far less. Although autopsy has a limited role in determining the cause of death in autopsies performed for anesthesia malpractice allegations, it can show that anesthesia has no role in the results by revealing others factors if factors such as patient and/or surgery have a role. There are a lot of studies showing that both allegations and antemortem diagnosis might change after autopsy. Any malpractice due to anesthesia or surgery practice as well as any condition other than the pathology leading to the operation and previously determined pathological condition should be questioned. In autopsies performed for malpractice allegations due to anesthesi-a, although autopsy has limitations in assessment of cause of death in cases of which anesthesia is suspected to be responsible, it has undoubtedly a very important place in anesthesia deaths in clarifying factors related to patient and surgery which constitute the dynamics of perioperative period.Key words: Autopsy, anesthesia, medical malpractice
Keywords: autopsy; anesthesia; medical malpractice